Assessment of electric field on polymeric insulator in polluted environment - Mohamed Zin, Nur Izzatul Huda (2021)
Insulators are among the most important electrical power transmission systems. Polymeric insulators are essential for better performance. Insulating polymers are widespread due to the wide range such as lightness, ease of installation and lower cost. Despite this advantage, the major cause of polymeric insulator failure is due to the polymer material aging and degradation which is caused by electrical stress on the high voltage terminal of the insulator. Thus, this project seeks to analyze the electrical field along the surface of the polymer insulator in the polluted environment. This can be achieved by creating a two-dimensional (2D) axisymmetric model by using Finite Element Tool COMSOL Multiphysics software. The results showed that the effect of uniform pollution layer with different thickness and conductivity on electrical along the insulator surface as the pollution layer thickness and conductivity electric field intensity increases. Electric fields along the insulator surface are highly influenced by the values of pollution layer conductivity and thickness. This indicates that effect of the dry band insulator surface towards electric field in a polluted environment shown the electric field is greatly influenced by the location of the dry band. The main goal is to evaluate the effect of uniform pollution layers with various thickness and conductivity and also analyze the effect of dry band insulator surface towards electric field performance in a polluted environment.